Hot-Melt Extrusion of the Thermo-Sensitive Peptidomimetic Drug Enalapril Maleate - Lena Hoffmann; Jörg Breitkreutz; Julian Quodbach (Pharmaceutics, 2022)
The aim of this research was the production of extrudates for the treatment of hypertension and heart failure and the investigation of the degradation of the peptidomimetic drug enalapril maleate (EM) during hot-melt extrusion (HME). A fast HPLC method was developed to quantify enalapril maleate and possible degradation products. Screening experiments revealed that the diketopiperazine derivative (Impurity D) was the main degradation product. Hot-melt extrusion of enalapril maleate with the polymer Soluplus® enabled extrusion at 100 °C, whereas a formulation with the polymer Eudragit® E PO could be extruded at only 70 °C. Extrusion at 70 °C prevented thermal degradation. A stabilizing molecular interaction between enalapril maleate and Eudragit® E PO was identified via FT-IR spectroscopy. Dissolution studies were carried out to study the influence of the formulation on the dissolution behavior of enalapril maleate. These promising results can be transferred to other thermo-sensitive and peptidomimetic drugs to produce extrudates which can be used, for instance, as feedstock material for the production of patient-specific dosage forms via Fused Deposition Modeling (FDM) 3D printing.